(untitled) (Journal of Energy and Safety Technology (JEST), 2023)
Employees play important roles regarding safety culture in the manufacturing industry. The study was conducted among 108 manufacturing workers and aimed to determine employees’ perceptions of safety culture in the manufacturing industry. The data obtained were analysed to see the relationship between sociodemographic factors and safety culture dimensions to safety performance. The four aspects of perception include four dimensions of management commitment, employee engagement, communication, and training and education. Demographic factors such as age and duration of work were not significantly related to variables related to staff perceptions (p > 0.05). In addition, the relationship between aspects of security culture dimensions and safety performance showed that there was a significant relationship between communication having the highest relationship (r = 0.403, P < 0.01) and the lowest relationship by management commitment dimension (r = 0.244, p < 0.01). The overall a grand total of these studies show a significant positive relationship with workers’ safety in the workplace (r = 0.377, p < 0.01). Therefore, companies are encouraged to increase training programs in the workplace to raise awareness of workplace hazard awareness as well as ongoing health and safety programs through helpful channels for employees to reduce workplace accidents.